Three Weeks of rTMS Treatment Maintains Clinical Improvement But Not Electrophysiological Changes in Patients With Depression: A 6-Week Follow-Up Pilot Study - Choi, Kyung Mook; Choi, Soo-Hee; Lee, Sang Min; Jang, Kuk-In; Chae, Jeong-Ho (Frontiers in Psychiatry, 2019)
Our previous study demonstrated that 3 weeks of repetitive transcranial magnetic stimulation (rTMS) increases P200 amplitudes and improves the symptoms of depression and anxiety in depression patients. In the present study, we investigated whether 3 weeks of rTMS treatment maintained the P200 amplitude in patients with depression at 6 weeks of follow-up. We measured the 6-week maintenance effects of rTMS using clinical questionnaires and an auditory oddball paradigm. Twenty-one patients with medication-resistant major depression participated in this pilot study. All patients underwent rTMS treatment for 3 weeks; they completed clinical ratings and performed the auditory oddball task at the pre-treatment, post-treatment, and 6-week follow-up visit (3 weeks after finishing rTMS treatment). The results revealed an increase in P200 amplitudes as well as improvements in the symptoms of depression and anxiety by 3 weeks of rTMS treatment. Furthermore, the results demonstrated maintenance effects on clinical ratings at 6-week follow-up. Depression and anxiety scales showed improvements in post-treatment and maintenance effects at the 6-week follow-up. The state anxiety scale decreased after rTMS treatment and showed maintenance effects at the 6-week follow-up. Although P200 amplitude showed a significant main effect for 3 time points (baseline, post-treatment, and 6-week follow-up visit), at 2 time points comparisons, P200 amplitudes significantly increased compared to those of the baseline condition, but did not show the maintenance effects of long-term rTMS at the 6-week follow-up compared to those of the baseline condition (p = .173, Bonferroni correction). Standardized low-resolution brain electromagnetic tomography (sLORETA) for P200 showed significant activation in the left middle frontal gyrus during 3 weeks of rTMS treatment, but no significant activation at the 6-week follow-up. Moreover, the amplitudes of overall topographic distribution were reduced at 6 weeks of follow-up. The 3 weeks of rTMS treatment induced the maintenance of the improvements in the symptoms of depression and anxiety. However, considering the results of the event-related potential (ERP) and sLORETA, 3 weeks of rTMS treatment may not be sufficient to maintain this improvement, implying that a treatment period of more than 3 weeks may be required to reveal the electrophysiological maintenance effect of rTMS.